The Heterogeneous Employment Outcomes of First- and Second-Generation Immigrants in Belgium - Céline Piton; Francois Rycx (Institute of Labor Economics (IZA), 2020)
This paper provides a comprehensive quantitative assessment of the employment performance of first- and second-generation immigrants in Belgium compared to that of natives. Using detailed quarterly data for the period 2008-2014, we find not only that first-generation immigrants face a substantial employment penalty (up to -36% points) vis-à-vis their native counterparts, but also that their descendants continue to face serious difficulties in accessing the labour market. The social elevator appears to be broken for descendants of two non-EU-born immigrants. Immigrant women are also found to be particularly affected. Among the key drivers of access to employment, we find: i) education for the descendants of non-EU-born immigrants, and ii) proficiency in the host country language, citizenship acquisition, and (to a lesser extent) duration of residence for first-generation immigrants. Finally, estimates suggest that around a decade is needed for the employment gap between refugees and other foreign-born workers to be (largely) suppressed.
Keywords: J15; J16; J21; J24; J61; 330; first- and second-generation immigrants; employment; moderating factors